Paediatric vulval lichen sclerosus: a retrospective study. (8th January 2019) - Ismail, D.; Owen, C. M.
Summary: Background: Lichen sclerosus (LS) is a chronic inflammatory dermatosis with a predilection for the anogenital region, which mainly affects prepubertal girls and postmenopausal women. The cause is unknown, but a number of potential aetiological factors have been identified. Aim: To examine a cohort of patients with prepubertal‐onset vulval LS (VLS) and assess baseline characteristics, clinical presentation, potential precipitating and predisposing factors, and response to treatment. Methods: Data were collected from case notes on patients aged < 18 years diagnosed with prepubertal‐onset VLS attending a specialist vulval dermatology service. Data included clinical presentation, comorbidities, family history, therapy and response to treatment. Results: In total, 26 paediatric patients were identified. The median age at onset of symptoms was 5 years (range 2–8.5 years). Many previously identified potential aetiological factors for the development of VLS were identified, including family history, trauma, autoimmune disease and hormonal factors. A significant proportion of patients had a history of urinary tract symptoms, including incontinence and urinary tract infection. Most patients responded well to a standard course of induction topical therapy followed by maintenance therapy, but some, including three patients with ongoing urinary incontinence and three postpubertal patients, continued to have active disease. Conclusion: A detailed assessment is essential in patients with VLS so that potential predisposing factors and comorbidities can be identified and managed. Urinary incontinence may be implicated in the development of paediatric VLS and may prevent adequate disease control. Paediatric VLS can persist through puberty, thus long‐term follow‐up is advised.